Safe Sexual Behaviors for Early Detection and Prevention of HIV/AIDS Transmission among Queers in Tulungagung, East Java, Using Theory of Planned Behavior - Widya Lusi Arisona; Argyo Demartoto; Bhisma Murti (Masters Program in Public Health, 2017)
Background: Sexual intercourse is one of the primary modes of HIV transmission. Sexual activity among heterosexuals has the highest risk of HIV transmission. However, sexual activity among queers also contributed much of the HIV/AIDS case increase. The prevalence of HIV/AIDS infection was high among queers in Tulungagung, East Java. This study aimed to examine safe sexual behaviors for early detection and prevention of HIV/AIDS transmission among queers using Theory of Planned Behavior.Subjects and Method: This was a qualitative study with phenomenology approach. The study was carried out at queers’ peer group namely Aprikot basecamp, Tulungagung, East Java, from 23 April to 17 June, 2017. The informants in this study included queers with positive HIV status and those with negative HIV status. These informants consisted of queer commercial sex workers, queers with steady partner, queers who had recently been registered as Apricot members, queers who had become Apricot members for long, Cesmid NGO, program manager of Local Commision for AIDS Control, health personnels, and officers at District Health Office Tulungagung. The informants were selected by maximum variation sampling. The data were collected using in-depth interview, observation, and document review methods. The data were analyzed by interactive analysis method, including data collection, data reduction, data display, and verification.Results: Five queer informants who worked as commercial sex workers were HIV positive. A queer informant who owned beauty salon had a steady partner. In general, queers had positive attitude towards early detection and prevention of HIV by undertaking regular three monthly HIV tests. The subjective norm in the community was very influential such that all Apricot members always complied with every rule available in the community. As a result, the queers had a stronger intention to do HIV early detection and prevention.Conclusion: Subjective norm is an important determinant for HIV early detection and prevention among queers. It is suggested that the positive norm in the community pertinent to sexual behavior be capitalized and strengtened so as to increase adherence to healthy and safe sexual behaviors among the queers.Keywords: risky sexual behaviors, early detection, prevention, HIV/ AIDS, queerCorrespondence: Widya Lusi Arisona. Masters Program in Public Health, Sebelas Maret University, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: widyalusi@gmail.com. Mobile: +6285646430617.Journal of Epidemiology and Public Health (2017), 2(2): 164-173https://doi.org/10.26911/jepublichealth.2017.02.02.07